2016
DOI: 10.3389/fphar.2016.00261
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Attenuates Beta-Amyloid-Induced Neuroinflammation via Activation of Peroxisome Proliferator-Activated Receptor-Gamma Function in a Rat Model of Alzheimer's Disease

Abstract: Neuroinflammation is known to have a pivotal role in the pathogenesis of Alzheimer's disease (AD), and curcumin has been reported to have therapeutical effects on AD because of its anti-inflammatory effects. Curcumin is not only a potent PPARγ agonist, but also has neuroprotective effects on cerebral ischemic injury. However, whether PPARγ activated by curcumin is responsible for the anti-neuroinflammation and neuroprotection on AD remains unclear, and needs to be further investigated. Here, using both APP/PS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 40 publications
1
79
0
Order By: Relevance
“…Liu and colleagues (2016) [95] studied the curcumin’s effects against neuroinflammation in both APP/PS1 transgenic mice and beta-amyloid-induced neuroinflammation in mixed neuronal/glial cultures. They showed that curcumin significantly alleviated spatial memory deficits in APP/PS1 mice and promoted cholinergic neuronal function in vivo and in vitro .…”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Liu and colleagues (2016) [95] studied the curcumin’s effects against neuroinflammation in both APP/PS1 transgenic mice and beta-amyloid-induced neuroinflammation in mixed neuronal/glial cultures. They showed that curcumin significantly alleviated spatial memory deficits in APP/PS1 mice and promoted cholinergic neuronal function in vivo and in vitro .…”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…Circular dichroism and co-immunoprecipitation analysis showed that curcumin directly bound to PPARγ and increased the transcriptional activity and protein levels of PPARγ. Taking together, these data suggested that PPARγ might be a potential target of curcumin, acting to alleviate neuroinflammation and improve neuronal function in AD [95]. …”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…Peroxisome proliferator‐activated receptor gamma (PPAR‐γ) is a ligand‐activated transcriptional factor that belongs to the nuclear hormone receptor superfamily. PPAR‐γ influences the activity of several intracellular second messengers and their signaling cascade, including regulation of insulin sensitivity, glucose homeostasis, fatty acid oxidation, immune responses, redox balance, cardiovascular integrity, and cell fate . Recent studies have reported that activation of PPAR‐γ reduces the development and progression of neurodegenerative diseases by altering the expression of NF‐κB cascade .…”
Section: Ppar γ As a Therapeutic Target In Neurodegenerative Diseasesmentioning
confidence: 99%
“…PPAR-γ influences the activity of several intracellular second messengers and their signaling cascade, including regulation of insulin sensitivity, glucose homeostasis, fatty acid oxidation, immune responses, redox balance, cardiovascular integrity, and cell fate. [130][131][132] Recent studies have reported that activation of PPAR-γ reduces the development and progression of neurodegenerative diseases by altering the expression of NF-κB cascade. 131,133,134 PPAR-γ is highly expressed in hippocampal region of the brain.…”
Section: Ppar γ As a Therapeutic Target In Neurodegenerative Diseasmentioning
confidence: 99%
See 1 more Smart Citation